Efektivitas Program Pendaftaran Tanah Sistematis Lengkap (PTSL) di Badan Pertanahan Nasional (BPN) Aceh Barat - Nindha Almira; Nurhaslita Sari (Pencerah, 2022)
The Complete Systematic Land Registration Program is a simultaneous land registration activity for the first time throughout Indonesia in one village area where there are still people whose land has not been registered. The Complete Systematic Land Registration Program has been regulated in Presidential Instruction Number 2 of 2018 concerning Acceleration of Complete Systematic Land Registration throughout Indonesia. The purpose of this program is to accelerate the provision of legal certainty and legal protection of community lands in a sure, fair and safe manner. And this study aims to determine the effectiveness of the PTSL program at the West Aceh National Land Agency. This study uses qualitative research methods with a descriptive approach and data collection is done by interview. The results obtained in this study are the implementation of the PTSL program at the National Land Agency of West Aceh has been carried out in accordance with the Regulation of the Minister of Agrarian Affairs and Spatial Planning Number 12 of 2017 and the stages of implementing the PTSL program such as planning for location determination, preparation, formation and appointment of the Land Registration Adjudication Committee. Complete Systematic, counseling, physical and juridical data collection, data research/land inspection, completion of PTSL activities, recognition and granting of rights, bookkeeping and certificate issuance. Based on the research results, the implementation of the PTSL program at BPN Aceh Barat has been effective.